Does the WTO Have a Future? - Unterhalter, David (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2025)
The World Trade Organization (WTO), once central to fostering global integration and growth, now faces profound challenges. Trade negotiations are paralyzed: the Doha Round collapsed, and members remain divided on pressing issues such as climate, digital trade, and subsidies. Since 2020, the Appellate Body has been defunct, leaving disputes unresolved and undermining trust in the system. The United States, historically the WTO’s main supporter, now disregards its rules with unilateral tariffs, while regional and bilateral agreements proliferate, fragmenting the multilateral order and disadvantaging weaker economies. The article argues that the WTO’s survival depends on moving beyond its current dysfunctions. The reliance on consensus as the basis of decision-making has become a recipe for paralysis. The author calls for greater use of multilateral agreements to break deadlock. The trade rulebook is also outdated and must be modernized, especially regarding subsidies and new challenges like digital trade and climate. Finally, the dispute settlement must be restored, whether through reforming the Appellate Body or reinforcing alternatives like the Multi-Party Interim Appeal Arbitration Agreement. Ultimately, the WTO’s future hinges on its ability to adapt. This paper argues that without institutional renewal and a willingness to abandon rigid practices that no longer serve, the organization risks irrelevance in a world where trade is increasingly governed by power dynamics rather than rules.